Effectiveness of midwifery-led care on pregnancy outcomes in low- and middle-income countries: a systematic review and meta-analysis - Rekiku Fikre; Jessica Gubbels; Wondwosen Teklesilasie; Sanne Gerards (BMC, 2023)
Abstract Background Midwifery-led care is an evidence-based practice in which a qualified midwife provides comprehensive care for low-risk pregnant women and new-borns throughout pregnancy, birth, and the postnatal period. Evidence indicates that midwifery-led care has positive impacts on various outcomes, which include preventing preterm births, reducing the need for interventions, and improving clinical outcomes. This is, however, mainly based on studies from high-income countries. Therefore, this systematic review and meta-analysis aimed to assess the effectiveness of midwifery-led care on pregnancy outcomes in low- and middle-income countries. Methods We used the Preferred Reporting Items for Systematic Review and Meta-Analysis (PRISMA) guidelines. Three electronic databases (PubMed, CINAHL, and EMBASE) were searched. The search results were systematically screened by two independent researchers. Two authors independently extracted all relevant data using a structured data extraction format. Data analysis for the meta-analysis was done using STATA Version 16 software. A weighted inverse variance random-effects model was used to estimate the effectiveness of midwifery-led care on pregnancy outcomes. Odds ratio with a 95% confidence interval (CI) was presented using a forest plot. Results Ten studies were eligible for inclusion in this systematic review, of which five studies were eligible for inclusion in the meta-analysis. Women receiving midwifery-led care had a significantly lower rate of postpartum haemorrhage and a reduced rate of birth asphyxia. The meta-analysis further showed a significantly reduced risk of emergency Caesarean section (OR = 0.49; 95% CI: 0.27-0.72), increased odds of vaginal birth (OR = 1.14; 95% CI: 1.04-1.23), decreased use of episiotomy (OR = 0.46; 95% CI: 0.10-0.82), and decreased average neonatal admission time in neonatal intensive care unit (OR = 0.59; 95% CI: 0.44-0.75). Conclusions This systematic review indicated that midwifery-led care has a significant positive impact on improving various maternal and neonatal outcomes in low- and middle-income countries. We therefore advise widespread implementation of midwifery-led care in low- and middle-income countries.